A History of Style and a Style of History: The Hermeneutic of Tarz in Persian Literary Criticism. Issue 2 (April 2022) - Farghadani, Shahla
Abstract: This article considers style in Persian literary history and its critical rhetorical and hermeneutical roles for poets and critics in the medieval and Safavid-Mughal eras. It explores how tarz (manner) emerged as a hermeneutical term in the thirteenth and fourteenth centuries and achieved a central position in sukhansanjī (evaluating speech) in the seventeenth and eighteenth centuries. This account of tarz —grounded in its historicity and multivalent implications—offers new insights into language for early modern Persian literary history, which is often periodized as sabk-i hindī (Indian style) or tāza-gūyī (fresh-speaking). Through a close reading of Safavid-Mughal tazkira s (literary compendiums), this contribution examines tarz as an operating concept deployed by a number of prominent tazkira writers. Finally, the article concludes by discussing this legacy's impact on twentieth-century scholarship.